UTERINE LEIOMYOSARCOMA - A CASE REPORT - T, HEERA SHENOY; SHIVAKUMAR; KAILASH, NISHI; ANTONY V, ABHILASH; HASHIM BH, HIBA; VALIYAKATH, FATHIMA; A KHADER, RESLIN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Leiomyomas are the most common mesenchymal neoplasms. Smooth muscle cells with variable amounts of fibrous stroma make up these benign tumors. The tumor occurs most frequently in uterus in 20–30% of women of reproductive age. Uterine leiomyosarcoma (uLMS/LMS) is a rare cancer originating from smooth muscle lining the walls of the uterus. We report a case of postmenopausal women of 65 years presented with retention urine, diagnosed as LMS of uterus on histopathology.